KEBIJAKAN PENGELOLAAN SUMBER DAYA PERIKANAN LAUT UNTUK MENUNJANG KETAHANAN PANGAN DI INDONESIA - Dewi Wuryandani; Hilma Meilani (Jurnal Ekonomi & Kebijakan Publik, 2011)
Fishery potential in this republic is very abundant in inland waterways andat sea, but until now has not been used optimally for the welfare of thepeople. Increased exports of fishery products has increased along withincreasing the standards required, both for fishery products in the countryand abroad who want quality and quality assured. Some classical problemsoften faced by this nation as production costs are still high, weakcapitalization, poor fish farming skills, a good seed, feed, disease,environmental management and post-harvest cultivation. In addition, withan increasingly open market in each country becomes a challenge for thenational fisheries development. If this issue is not addressed, it is notpossible to inhibit the increasing competitiveness of fisheries sector in thefuture.